135 Detecting Progression of Diffuse Interstitial Fibrosis in Alstrom Syndrome. (3rd June 2016) - Baig, Shanat; Edwards, Nicola; Liu, Boyang; Hayer, Manvir; Dawson, Charlotte; Geberhiwot, Tarekegn; Steeds, Richard
Abstract : Introduction: Alstrom Syndrome (ALMS) is a rare inherited disorder caused by a mutation in the ALMS1 gene. The syndrome is a multi-system disorder with exaggerated features of the metabolic syndrome and although rare, provides a monogenic model for end-organ fibrosis and as a paradigm for the effects of severe metabolic syndrome. Adults with ALMS have a high risk of death from heart failure in their twenties due to a cardiomyopathy which (in the small post-mortem series available) is characterised by coarse fibrosis on histology. Our previous work has identified expansion of the extracellular space (ECV) consistent with diffuse interstitial fibrosis in over half of asymptomatic ALMS patients compared to controls. The aim of this study was to investigate the longitudinal change in ECV and assess the impact on ventricular structure and function. Methods: A prospective longitudinal cohort study of patients attending the national service for ALMS at the Centre for Rare Disease in Birmingham from 2012. At referral and on annual follow up, all subjects underwent comprehensive LV and RV assessment with cardiac MRI (CMR 1.5T Siemens Avanto). The presence of diffuse interstitial myocardial fibrosis was assessed using native myocardial T1 relaxation mapping and extracellular volume (ECV) in the LV septum (MOLLI) using cvi42 (Circle Cardiovascular Imaging). Coarse replacement fibrosis was assessed using standard late gadolinium enhancement imaging. Results: In total 14 patients (male gender 71%, age 28 ± 8years) had baseline and follow up data (median 1.7 [1.1–2.8] years). CMR data is presented in Table 1. The native LV myocardial T1 values and ECV were increased in the septum at basal and mid levels at follow up. Left ventricular mass increased (54 ± 9 g/m 2 vs. 62 ± 12 g/m 2 ) but with a reduction in septal myocardial intracellular volume (ICV 0.74 ± 0.06 vs. 0.68 ± 0.04, p < 0.05) suggesting ECV expansion rather than myocyte hypertrophy was the driver. There were no differences in LV or RV volumes or RVEF. Four patients had LGE; two patients had focal at RV insertion points LGE and two patients had mid-wall LGE in the basal infero-lateral segments. Conclusion: ALMS is associated with increases in ECV and progressive change in T1 values over time that reflects progression of diffuse interstitial fibrosis in asymptomatic adults. Cross-sectional studies have identified ECV as a biomarker of cardiovascular "vulnerability" but longitudinal tracking has the potential to highlight those at greatest risk.